Intraoperative Optical Coherence Tomography (OCT): A New Frontier in Vitreo-Retinal Surgery - Vinod Kumar; Amit Gadkar; Parijat Chandra; Atul Kumar (Delhi Journal of Ophthalmology)
Optical coherence tomography, a non-invasive imaging technique is an indispensable tool in the armamentarium of modern day ophthalmologists. With evolution in technology, modern day OCT machines (swept source OCT) are able to provide high resolution images of vitreous, retina, choroid and sclera simultaneously. As a better understanding of various retinal disorders was obtained with the use of OCT, the need for refinement of vitreo-retinal surgery utilizing intra-operative OCT was felt. While earlier versions of intra-operative OCT were hand held, the newer versions are fully integrated with microscope (MIOCT). MIOCT provides spectral-domain OCT (SD-OCT) images while performing the surgery on heads up display. MIOCT has been found to be useful in the management of various disorders such as macular hole, epiretinal membrane, vitreomacular traction syndrome, vitreous hemorrhage and retinal detachment. However the present day intraoperative OCT machines have several limitations, which need to be sorted out before they can be incorporated in the daily practice.